2013
DOI: 10.1177/0954405413479478
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of tool wear and surface roughness during machining of ZA43–SiCp composite using full factorial approach

Abstract: This article presents the study of machinability of ZA43 alloy reinforced with silicon carbide particulate metal matrix composites. The specimen was fabricated through conventional liquid metallurgy technique. Silicon carbide with particle size of 60 mm with three different weight percentages (i.e. 5%, 10%, and 15%) was used for fabrication. Dry turning of composite specimens was carried out using uncoated and coated carbide indexible inserts on a conventional lathe. Comparisons of performance of each grade of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…10 An increased amount of SiC reinforcement resulted in a higher tool-work interface temperature and higher cutting forces. A study on the machinability of a ZA43 alloy reinforced with SiC particles (size: 60 mm; 5-15 wt%) during dry turning by uncoated and coated carbides 11 showed that the cutting speed, feed rate and depth of cut affected both surface finish and tool wear.…”
Section: Introductionmentioning
confidence: 99%
“…10 An increased amount of SiC reinforcement resulted in a higher tool-work interface temperature and higher cutting forces. A study on the machinability of a ZA43 alloy reinforced with SiC particles (size: 60 mm; 5-15 wt%) during dry turning by uncoated and coated carbides 11 showed that the cutting speed, feed rate and depth of cut affected both surface finish and tool wear.…”
Section: Introductionmentioning
confidence: 99%
“…A parameter that represents the material properties can be defined by dividing the hardness by the elongation. Therefore, a three-factor, full-factorial design 15,16 methodology was used to investigate the influences of the material hardness and elongation, spindle speed and feed rate on the fractal dimension and surface roughness of the finished surface. The advantages of a full-factorial analysis include the greater amount of information provided, more accurate experimental results and more reliable conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…9 Research works into improving or quantifying the machinability of MMCs that has been undertaken since the early 1970s. [10][11][12][13] This is especially useful since carbide inserts are cheaper, and tool wear starts relatively quickly, allowing the evaluation of different parameters in order to determine their machinability and suitability for critical conditions. This is also ideal for evaluating the effects of cooling methods under similar conditions.…”
Section: Introductionmentioning
confidence: 99%